FEED RATION HOMOGENEITY DURING DISTRIBUTION OF BROILERS' AUTOMATIC FEEDERS - CARDINAL, K.M.; VALE, M.M.; ALONÇO, A.S.; BORILLE, R.; KLEIN, D.R.; NAAS, I.A. (Revista Brasileira de Engenharia de Biossistemas, 2014)
The study aimed to verify the efficiency of two equipment distributors of feed for broilers. Feed samples were collected from two broiler automatic feeder dish, with similar characteristics but different manufacturers. The samples were collected from five points of distribution, namely: storage silo, hopper, the first dish, the middle and the last dish. The samples were subjected to quantitative analysis of ashes and particle size analysis. The data were subjected to analysis of variance (ANOVA), means separated by Tukey test with p <0.01, and analysis of linear regression. The results of statistical ashes analyze show that there is a significant difference in granule size and the amount of ashes. Can be concluded that are segregation of the feed during distribution along the route, being that there is the accumulation of ashes in the first dishes and content decreases as the distribution. The particle size showed the opposite result of ashes, with larger granules in the last dish and smaller granule size at the first dish.